Maerua angolensis DC. (Capparaceae): A Review of its Medicinal Uses, Phytochemistry and Pharmacological Properties - Alfred Maroyi (Journal of Pharmacy and Nutrition Sciences, 2020)
Maerua angolensis DC. is collected from the wild for its edible leaves and fruits, and is also used as a traditional medicine. This study is aimed at evaluating the ethnomedicinal uses, phytochemistry and pharmacological properties of M. angolensis. Results of the current study are based on data derived from several online databases such as Scopus, Google Scholar, PubMed and Science Direct, and pre-electronic sources such as scientific publications, books, dissertations, book chapters and journal articles. The articles published between 1960 and 2020 were used in this study. This study revealed that the aerial parts, bark, leaves, roots and stem bark infusion and/or decoction of M. angolensis are mainly used as a protective charm and ethnoveterinary medicine, and a traditional medicine for pain, cancer, fever, malaria, sores, wounds and gastro-intestinal problems. Phytochemical compounds identified from the species include alkaloids, amino acids, anthraquinones, betaines, cardiac glycosides, cyanidin, esters, fatty acids, flavonoids, glucosinolates, phenols, saponins, sterols, steroids, tannins and triperpenoids. Ethnopharmacological research revealed that M. angolensis extracts have acaricidal, anthelmintic, antibacterial, antifungal, antidiarrhoeal, anticonvulsant, anti-diabetic, antidepressant, anti-inflammatory, antioxidant, antinociceptive, anxiolytic, anti-urolithiatic, antiprotozoal, molluscicidal and nematicidal activities. There is need for extensive toxicological evaluations of crude extracts and compounds isolated from the species since M. angolensis contains potentially toxic compounds